2004
DOI: 10.1097/00000542-200409000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Inhibits Phorbol-Myristate-Acetate-induced Activator Protein-1 Activation in Human T Lymphocytes in Vitro : Potential Role of the p38-Stress Kinase Pathway

Abstract: The data demonstrate that sevoflurane is a specific inhibitor of AP-1 and may thus provide a molecular mechanism for the antiinflammatory effects associated with sevoflurane administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 52 publications
1
31
2
1
Order By: Relevance
“…Protocol of A549 cell exposure to sevoflurane A549 cells in the exponential growth phase were inoculated onto plates and cultured in a CO 2 incubator (ThermoFisher Scientific, Waltham, MA) for 24 h. In accordance with the experimental protocol previously described [14,15], cell culture plates were placed in an airtight glass chamber with inlet and outlet connectors. The inlet port of the chamber was connected to the anesthesia machine (Cicero-EM 8060; Dräger, Germany), and sevoflurane was supplied into the chamber by a sevoflurane vaporizer (Sevorane; Abbott, Abbot Park, IL) attached to the anesthesia machine.…”
Section: Cell Line and Cell Culturementioning
confidence: 99%
“…Protocol of A549 cell exposure to sevoflurane A549 cells in the exponential growth phase were inoculated onto plates and cultured in a CO 2 incubator (ThermoFisher Scientific, Waltham, MA) for 24 h. In accordance with the experimental protocol previously described [14,15], cell culture plates were placed in an airtight glass chamber with inlet and outlet connectors. The inlet port of the chamber was connected to the anesthesia machine (Cicero-EM 8060; Dräger, Germany), and sevoflurane was supplied into the chamber by a sevoflurane vaporizer (Sevorane; Abbott, Abbot Park, IL) attached to the anesthesia machine.…”
Section: Cell Line and Cell Culturementioning
confidence: 99%
“…3 IV anesthetics except propofol and volatile anesthetics are known to augment surgically induced immunosuppression. [7][8][9][10] Ketamine by its adrenergic stimulatory properties promote tumourmetastasis.Propofol has no effect on metastasis due to its weak beta adrenergic antagonist properties. The antitumoural protective effect of propofol has been suggested due to its inhibitory effect on cycloxygenase 2 and PGE2 in cancer cells as well as stimulation of immunity response.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumoural protective effect of propofol has been suggested due to its inhibitory effect on cycloxygenase 2 and PGE2 in cancer cells as well as stimulation of immunity response. [7][8][9][10] Opioids by inhibiting cellular and humeral immunity and due to their proangiogenic effect by activation of Mu opioid receptors found in vascular endothelial cells may promote metastasis. 11,12 But the pain relief induced by them can attenuate the increased susceptibility for metastasis induced by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sevoflurane likely exerts anti-inflammatory activities on various types of cells. Notably, it has been suggested that sevoflurane exerts an anti-inflammatory action via the mechanisms involving the reduction of mRNA and protein levels of the proinflammatory transcription factors NF-κB and AP-1 (35,37).…”
Section: Discussionmentioning
confidence: 99%